2015
DOI: 10.1038/ncomms9172
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of alignment and structural changes of carbon disulfide molecules using ultrafast electron diffraction

Abstract: Imaging the structure of molecules in transient-excited states remains a challenge due to the extreme requirements for spatial and temporal resolution. Ultrafast electron diffraction from aligned molecules provides atomic resolution and allows for the retrieval of structural information without the need to rely on theoretical models. Here we use ultrafast electron diffraction from aligned molecules and femtosecond laser mass spectrometry to investigate the dynamics in carbon disulfide following the interaction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 50 publications
2
55
0
Order By: Relevance
“…The pulse duration is still short enough to operate in the regime of impulsive alignment. In a separate study, we have also observed that further increasing the laser intensity does not significantly increase the degree of alignment [27]. The center region (s < 1.0 Å -1 ) of the diffraction patterns is blocked by a beam stop, as shown in Figure 6.…”
Section: Methodsmentioning
confidence: 76%
“…The pulse duration is still short enough to operate in the regime of impulsive alignment. In a separate study, we have also observed that further increasing the laser intensity does not significantly increase the degree of alignment [27]. The center region (s < 1.0 Å -1 ) of the diffraction patterns is blocked by a beam stop, as shown in Figure 6.…”
Section: Methodsmentioning
confidence: 76%
“…Impulsive alignment can be improved by using a sequence of laser pulses [77], but is ultimately limited by the initial rotational temperature of the molecules and the maximum intensity that can be applied. Recent UED experiments have shown that impulsive alignment reaches a saturation value for intensities well below the ionization threshold, and that at high intensities the structure can be distorted by multiphoton excitation [25]. Another option to improve the alignment is a mixed alignment with shaped laser pulses to do adiabatic turnon and impulsive turn-off of the alignment field [78,79].…”
Section: Structure Retrieval and Improved Alignmentmentioning
confidence: 99%
“…The laser intensity is limited by multiphoton excitation and ionization events that can distort the molecular structure [25]. For small molecules in the gas phase, multiphoton ionization typically becomes significant at laser intensities around 10 13 W cm -2 [68].…”
Section: Imaging Of Molecules By Electron Diffraction From Impulsivelmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, structural evolutions during phase transitions have been mapped using ultrafast electron microscopy and crystallography [5][6][7]. Also, diffraction images have identified transient molecular structures [8] and established evidence of deformation and dissociation of molecules interacting with laser pulses [9]. Nowadays, electron pulses with femtosecond (fs) duration have been reported [10][11][12][13][14].…”
mentioning
confidence: 99%